2020
DOI: 10.1038/s41522-020-00147-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial electroactive biofilms dominated by Geoalkalibacter spp. from a highly saline–alkaline environment

Abstract: Understanding of the extreme microorganisms that possess extracellular electron transfer (EET) capabilities is pivotal to advance electromicrobiology discipline and to develop niche-specific microbial electrochemistry-driven biotechnologies. Here, we report on the microbial electroactive biofilms (EABs) possessing the outward EET capabilities from a haloalkaline environment of the Lonar lake. We used the electrochemical cultivation approach to enrich haloalkaliphilic EABs under 9.5 pH and 20 g/L salinity condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…A modified M9 medium with 20 g/L salinity and 9.5 pH was used as a catholyte or growth medium (200 mL) in the cathode chamber. Its composition is as follows (per L of distilled water): 4.33 g Na 2 HPO 4 , 2.69 g NaH 2 PO 4 , 20 g NaCl, 4.3 g Na 2 CO 3 , 0.13 g KCl, 0.31 g NH 4 Cl, 12.5 mL vitamins, and 12.5 mL trace elements ( Yadav and Patil, 2020 ). Sodium nitrate (10 mM) and sodium bicarbonate (10 mM) were used as the terminal electron acceptor (TEA) and carbon source, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified M9 medium with 20 g/L salinity and 9.5 pH was used as a catholyte or growth medium (200 mL) in the cathode chamber. Its composition is as follows (per L of distilled water): 4.33 g Na 2 HPO 4 , 2.69 g NaH 2 PO 4 , 20 g NaCl, 4.3 g Na 2 CO 3 , 0.13 g KCl, 0.31 g NH 4 Cl, 12.5 mL vitamins, and 12.5 mL trace elements ( Yadav and Patil, 2020 ). Sodium nitrate (10 mM) and sodium bicarbonate (10 mM) were used as the terminal electron acceptor (TEA) and carbon source, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported on the electrotrophic mixed-culture microbial biofilms, grown with electron acceptors such as oxygen ( Rabaey et al., 2008 ), H + ions ( Aulenta et al., 2008 ), CO 2 ( Aryal et al., 2017 ), heavy metals, polyaromatic hydrocarbons, dyes, and so on ( Gregory and Lovley, 2005 ; Tandukar et al., 2009 ; Sharma et al., 2020 ; Fang et al., 2016 ). Notably, EAMs have been studied mostly from nonextreme environments, and only a few studies have reported the diversity of these microbes inhabiting extreme habitats ( Koch and Harnisch, 2016 ; Rowe et al., 2017 ; Logan et al., 2019 ; Yadav and Patil, 2020 ). In particular, electrotrophs from extreme habitats have been barely studied, limiting our understanding of EET-capable microbes and their role in element cycling under specific environmental conditions and their use for various BES applications.…”
Section: Introductionmentioning
confidence: 99%
“…Depending upon the mode of EET, EAMs are categorized as exoelectrogens and electrotrophs. Exoelectrogens can transfer electrons to a solid-state electron acceptor, and electrotrophs can oxidize a solid-state electron donor ( Logan et al., 2019 ; Yadav and Patil, 2020 ). Bioelectrochemical systems (BESs) are routinely used in laboratories to study the electroactive nature of microorganisms and explore them for various applications ( Yee et al., 2020 ).…”
Section: Before You Beginmentioning
confidence: 99%
“…This protocol describes the electrochemical enrichment and characterization of nitrate-reducing electrotrophs from the highly saline and alkaline environment of Lonar Lake. The protocol has been adapted from various other papers on the enrichment of different types of EAMs (e.g., Karbelkar et al., 2019 ; Gregory et al., 2004 ; Yadav and Patil, 2020 ). It mainly targets the growth of cathodic microbial biofilm, provided with a suitable terminal electron acceptor (TEA), i.e., nitrate.…”
Section: Before You Beginmentioning
confidence: 99%
See 1 more Smart Citation